(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Any orthodontic case must have anchoring carefully planned before beginning active treatment in order to eliminate potential issues during treatment. This article covered every facet of anchorage, including its definition, origins, types, planning, anchorage loss, and methods for preventing it.